Exploring the Experiences and Coping Strategies of People Living with HIV: A Qualitative Study from the Health Blog Post - Bakan, Gulcan; AK, Pınar Sercekus (Bangladesh Journal of Medical Science, 2025)
Objective HIV infection is considered a chronic disease and provision of appropriate care for people living with HIV is prioritized globally. The aim of this study is to describe experiences and coping strategies of people living with HIV in Turkey based on their blog posts. Materials and Methods The study has a qualitative design. Two hundred and fifty-three posts in a blog were examined. Data were collected by using document analysis. Results Findings were categorized into four themes: being diagnosed, difficulties experienced, coping and gains. They had some negative feelings after being diagnosed. While some participants reported to get sufficient support from their families, partners, friends and health professionals, others said that their friends did not want to meet up with them and that their families rejected them. Religious, beliefs, positive thinking and blog using by PLWH were found to be coping strategies. The blog users had a fear about transmitting the disease to other people and about possibility of their friends and relatives’ being diagnosed as HIV. They had some gains such as positive effects on their opinions about the value of life. Conclusions This qualitative study was the first to explore experience of PLWH in Turkish culture. It is of importance to determine what PLWH from different cultures experience to offer appropriate nursing care. Nurses need to be aware of the effect of blogs on patients. BJMS, Vol. 24 No. 03 July’25 Page : 792-798